After a Hand Was Lent: Sporadically Experiencing Multisensory Interference During the Rubber Hand Illusion Does Not Shield Against Disembodiment - Julia Eck; David Dignath; Andreas Kalckert; Roland Pfister (Journal of Cognition)
Observations from multisensory body illusions indicate that the body representation can be adapted to changing task demands, e.g., it can be expanded to integrate external objects based on current sensorimotor experience (embodiment). While the mechanisms that promote embodiment have been studied extensively in earlier work, the opposite phenomenon of, removing an embodied entity from the body representation (i.e., disembodiment) has received little attention yet. The current study addressed this phenomenon and drew inspiration from the partial reinforcement extinction effect in instrumental learning which suggests that behavior is more resistant to extinction when reinforcement is delivered irregularly. In analogy to this, we investigated whether experiencing occasional visuo-motor mismatches during the induction phase of the moving rubber hand illusion (intermittent condition) would result in slower disembodiment as compared to a regular induction phase where motor and visual signals always match (continuous condition). However, we did not find an effect of reinforcement schedule on disembodiment. Keeping a recently embodied entity in the body schema, therefore, requires constant updating through correlated perceptual and motor signals.